Typhoid spondylodiscitis mimicking tuberculosis in a teenage girl. Issue 1 (January 2018) - Banerjee, Barnini; Madiyal, Mridula; Madhava, Pai K; Agarwal, Manali; Mukhopadhyay, Chiranjay
Abstract: Salmonella Typhi cause a broad spectrum of human illnesses like gastroenteritis, typhoid fever, and bacteremia. It has also been recognized as a causative organism of osteomyelitis for more than a century but the incidence appears to be uncommon. Microbiological workup plays important role in the diagnosis of Typhoid spondylodiscitis as most of the time it mimics tuberculosis and misguide the clinician, especially in the developing world. Here, we reported an uncommon case of lumbar spondylodiscitis by Salmonella Typhi in an immunocompetent teenager, with the help of clinical, microbiological and radiological evidence. The case was managed conservatively after posterior spinal stabilization.